Deciphering the Regulatory Circuitry That Controls Reversible Lysine Acetylation in Salmonella enterica - Hentchel, Kristy L. (mBio, 2015)
In Salmonella enterica, the reversible lysine acetylation (RLA) system is comprised of the protein acetyltransferase (Pat) and sirtuin deacetylase (CobB). RLA controls the activities of many proteins, including the acetyl coenzyme A (acetyl-CoA) synthetase (Acs), by modulating the degree of Acs acetylation. We report that IolR, a myo-inositol catabolism repressor, activates the expression of genes encoding components of the RLA system. In vitro evidence shows that the IolR protein directly regulates pat expression. An iolR mutant strain displayed a growth defect in minimal medium containing 10 mM acetate, a condition under which RLA function is critical to control Acs activity. Increased levels of Pat, CobB, or Acs activity reversed the growth defect, suggesting the Pat/CobB ratio in an iolR strain is altered and that such a change affects the level of acetylated, inactive Acs. Results of quantitative reverse transcription-PCR (qRT-PCR) analyses of pat, cobB, and acs expression indicated that expression of the genes alluded to in the IolR-deficient strain was reduced 5-, 3-, and 2.6-fold, respectively, relative to the levels present in the strain carrying the iolR(+) allele. Acs activity in cell-free extracts from an iolR mutant strain was reduced ~25% relative to that of the iolR(+) strain. Glucose differentially regulated expression of pat, cobB, and acs. The catabolite repressor protein (Crp) positively regulated expression of pat while having no effect on cobB.